Parental alienation as a cause of variation of tenence - Fernández Espinoza, William Homer (2017)
This research study investigates parental alienation and its manifestation in the tenure processes and the visitation regime as a problem that violates the fundamental rights of children and adolescents. These were not recognized recognized in the legal system of our country, reason why, we maintain, should be regulated as a cause of the change in tenure.For its development, a field work was carried out and 14 judges of the family courts of the Superior Court of cadres and pie charts were surveyed on the results obtained for their contrast and discussion. Also the analysis of the doctrine, the legislation and the national and international jurisprudence on the subjects related to this investigation was realized.The description of problematic reality and the theoretical framework on parental alienation, parental authority, tenure processes and the visitation regime, and the integral protection of the rights of the child (mainly the right to live with the family) . In th